Analysis of the Characteristics of SARS-Cov-2 Spike Compared to SARS-Cov Spike and Its Role in the Pathogenesis of Infection– A Literature Review - Galih Kathleyana; Sihning E.J.T; Diah Purwaningsar; Retno Budiarti (Indian Journal of Forensic Medicine & Toxicology, 2021)
The spread of COVID-19 that caused by SARS-CoV-2 happened very fast & has infected many people. WHO reported 1,051,635 cases of COVID-19 and 56,985 confirmed deaths caused by COVID-19 as of April 4, 2020. SARS-CoV-2 is a novel coronavirus that originates from betacoronavirus together with SARS-CoV.This study aims to find and understand the differences between the SARS-CoV-2 and SARS-CoV spikes in the infection and the spread of the resulting disease. This is a literature studies obtained from national journal articles indexed by SINTA and international journals indexed by Scimago or Scopus and published in 2015-2020. We concluded that there is a difference between the SARS-CoV-2 spike and the SARS-CoV spike, so that it can affect the spread of the disease. SARS-CoV-2 has a furin cleavage site that absent in SARS-CoV. The existence of this furin cleavage site can help the activation and the efficiency of the infection of the SARS-CoV-2 and increases its transmissibility to organs and populations when compared to viruses without furin cleavage sites such as SARS-CoV.